Infographics as an Effective Tool for School History Education? - Nowocin, Jakub (Sensus Historiae, 2025)
The article focuses on the use of infographics in history lessons in a primary school. An original empirical study was proposed based on the history didactics. The main reason was to verify the effectiveness of infographics and determine their impact on students’ attitude towards history. The analysis of the conducted pedagogical experiment is preceded by a characterization of infographics as a form of knowledge visualization, as well as teaching aids. The study was carried out during a work placement in a primary school. It was constructed based on infographics included in school history textbooks as well as diagnostic tests, which were created as an appropriate measurement tool.